A variational theory of Hall effect of Anderson lattice model: Application to colossal magnetoresistance manganites (Re1−x Ax MnO3) - Panwar, Sunil; Kumar, Vijay; Singh, Ishwar (Solid state communications, 2017)
An anomalous Hall constant RH has been observed in various rare earth manganites doped with alkaline earths namely Re1−xAxMnO3 (where Re = La, Pr, Nd etc., and A = Ca, Sr, Ba etc.) which exhibit colossal magnetoresistance (CMR), metal- insulator transition and many other poorly understood phenomena. We show that this phenomenon of anomalous Hall constant can be understood using two band (ℓ-b) Anderson lattice model Hamiltonian alongwith (ℓ-b) hybridization recently studied by us for manganites in the strong electron-lattice Jahn-Teller (JT) coupling regime an approach similar to the two – fluid models. We use a variational method in this work to study the temperature variation of Hall constant RH (T) in these compounds. We have already used this variational method to study the zero field electrical resistivity ρ (T) and magnetic susceptibility of doped CMR manganites. In the present study, we find that the Hall constant RH (T) reduces with increasing magnetic field parameters h&m and the metal-insulator transition temperature (Tρ) shifts towards higher temperature region. We have also observed the role of the model parameters e.g. local Coulomb repulsion U, Hund’s rule coupling JH between eg spins and t2g spins, ferromagnetic nearest neighbor exchange coupling JF between t2g core spins and hybridization Vk between ℓ-polarons and d-electrons on Hall constant RH (T) of these materials at different magnetic fields. Here we find that RH (T) for a particular value of h and m shows a rapid initial increase, followed by a sharp peak at low temperature say 50K in our case and a slow decrease at high temperatures, resembling with the key feature of many CMR compounds like La0.8Ba0.2 MnO3.The magnitude of RH (T) reduces and the anomaly (sharp peak) in RH becomes broader and shifts towards higher temperature region on increasing Vk or JH or doping x and even vanishes on further increasing these parameters. Our results of anomalous Hall constant (RH) have same qualitative behavior as the zero-field electrical resistivity. Moreover Hall Constant (RH) shows positive values indicating that the carriers in these manganites are holes. •We use two band (ℓ-b) Anderson lattice model Hamiltonian alongwith (ℓ-b) hybridization recently studied by us for manganites in the strong electron-lattice Jahn-Teller (JT) coupling regime.•We use a variational method in this work to study the temperature variation of Hall constant RH (T) in these compounds.•We find that the Hall constant RH (T) reduces with increasing magnetic field parameters h&m and the metal-insulator transition temperature (Tρ) shifts towards higher temperature region.•We have also observed the role of the model parameters e.g. U, JH, JF and hybridization Vk between ℓ-polarons and d-electrons on Hall constant RH (T) of these materials at different magnetic fields.•Here we find that RH (T) for a particular value of h and m shows a rapid initial increase, followed by a sharp peak at low temperature say 50K in our case and a slow decrease at high temperatures, resembling with the key feature of many CMR compounds like La0.8Ba0.2 MnO3.